High-Intensity Intermittent Exercise and its Effects on Heart Rate Variability and Subsequent Strength Performance - Panissa, Valéria L. G.; Cal Abad, Cesar C.; Julio, Ursula F.; Andreato, Leonardo V.; Franchini, Emerson (Frontiers in Physiology, 2016)
PRUPOSE: To investigate the effects of a 5-km high-intensity interval exercise (HIIE) on heart rate variability (HRV) and subsequent strength performance. METHODS: nine trained males performed a control session composed of a half-squat strength exercise (4 x 80% of one repetition maximum – 1RM) in isolation and 30-min, 1-, 4-, 8- and 24-h after an HIIE (1-min at the velocity peak:1-min passive recovery). All experimental sessions were performed on different days. The maximum number of repetitions and total weight lifted during the strength exercise were registered in all conditions; in addition, prior to each session, HRV were assessed [beat-to-beat intervals (RR) and log-transformed of root means square of successive differences in the normal-to-normal intervals (lnRMSSD)]. RESULTS: Performance in the strength exercise dropped at 30-min (31%) and 1-h (19%) post-HIIE concomitantly with lower values of RR (781±79 ms; 799±134 ms, respectively) in the same recovery intervals compared to the control (1015±197 ms). Inferential analysis did not detect any effect of condition on lnRMSSD, however, values were lower after 30-min (3.5±0.4 ms) and 1-h (3.3±0.5 ms) with moderate and large effect sizes (0.9 and 1.2, respectively) compared with the control condition (3.9±0.4 ms). CONCLUSION: Both RR and lnRMSSD seem to be associated with deleterious effects on strength performance, although further studies should be conducted to clarify this association.